Estruturas secretoras de Pavonia alnifolia (Malvaceae), uma espécie ameaçada de extinção - Pimentel, Rafael Ribeiro; Machado, Silvia Rodrigues [UNESP]; Rocha, Joecildo Francisco (My University, 2011)
Malvaceae shows a rich morphological diversity of secretory structures, which are of great ecological and taxonomical relevance. Nonetheless, until the present moment, studies on the secretory structures of the studied species were not found. Pavonia alnifolia A.St.-Hil. is endangered species of extinction with restricted distribution within the restingas of Rio the Janeiro and Espírito Santo, Brazil. The species were collected from the former and usual techniques on plant anatomy and histochemistry were performed. Anatomical and histochemical studies of the secretory structures of Pavonia alnifolia are showed in this work. The presence of external and internal secretory structures of mucilage in many organs, idioblasts of phenolic and lipid substances and floral nectaries what is a very important adaptative survival mechanism of the species in the restinga environment. The secretion produced by nectaries is envolved with maintenance of interations with visiting insects, what constitutes a good model to experimental studies with an ecological approach.
Secretory structures in Pavonia alnifolia (Malvaceae), an endangered species of extinction
Keywords: Anatomy; Histochemistry; Marambaia; Pavonia; Secretory structures; Hexapoda; Malvaceae